Importancia de la fertilización fósforo – potásica, al suelo y foliar, para mejorar la producción del cultivo de soya (Glycine max M.) - Mosquera Vera, Alex Adrián (2025)
Soybean is currently the most important oilseed in the world, thanks to its quality and high protein content. The main objective of the research was to describe the importance of phosphorus-potassium fertilization, both in soil and on leaves, to improve soybean (Glycine max M.) crop production. For the preparation of the document, updated information was collected from scientific articles and virtual libraries. The conclusions determined that phosphorus plays a crucial role in the transfer of energy within plants, promoting healthy root growth and improving soybean tolerance to stress conditions such as drought and disease; potassium plays a crucial role in the yield and quality of the soybean crop, as it is essential for the activation of enzymes, osmotic regulation and the transport of assimilated substances such as starch and sugar, and for the metabolism of carbohydrates and proteins. Phosphorus (P) deficiency in soybean crops is related to biochemical reactions necessary for plant life and reproduction, such as chlorosis, stunting, poor grain formation and reduced pods per plant, limiting its yield potential, and potassium deficiency in soybeans results in a yellowish color in the lower leaves, leading to chlorostatic advance and necrosis. Deficient plants grow slowly, develop slowly and produce small and deformed grains.